IQTISODIY INQIROZLARNING SABABLARI VA ULARNI BARTARAF ETISH USULLARI (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article provides a detailed analysis of the causes of economic crises, their impact on the economy, and ways to overcome them. Various forms of crises, such as financial, production, energy, and trade crises, are examined along with their history and influence on the modern economy. Additionally, the role of government policies, innovations, international cooperation, and the digital economy as effective tools for combating crises is discussed. Based on historical examples, strategies for preventing economic crises in the future are outlined. This study includes relevant recommendations for ensuring economic stability and may be useful for researchers, students, and a broad audience interested in economics